Two-decade variability of climatic factors and its effect on the link between photosynthesis and meteorological parameters: example of Finland's boreal forest - Pysarenko, L.; Krakovska, S.; Savenets, M.; Ezhova, E.; Lintunen, A.; Petäjä, T.; Bäck, J.; Kulmala, M. (Boreal Environment Research Publishing Board, 2024)
Extreme temperature events over the eastern part of the Baltic Sea region during winter were examined in order to address how often these events may be related to the anomalies of stratospheric dynamics through their influence on the tropospheric circulation regime. The propagation of geopotential height anomalies between the stratosphere and the troposphere was evaluated using the Northern Annular Mode. It was determined that in over 60% of all analysed cases, the surface temperature anomalies are preceded by dynamical disturbances in the stratosphere. A strong relation between tropospheric winter temperature extremes and strength of the stratospheric polar vortex was detected up to 10 hPa. Finally, the stratospheric-tropospheric dynamic interaction was evaluated using analysis of Eliassen-Palm vertical wave activity fluxes at a 10 hPa pressure level. The role of the quasi-biennial oscillation phase in the formation of temperature anomalies was also estimated.